Peristomal plate cut mold: possibilities for applying new products (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Introduction: peristomal dermatitis can be caused by leakage between adhesive plate and skin. Objective: to describe the peristomal plate cut mold (PPCM) for simultaneous evaluation of new products for the treatment of dermatitis. Methods: experience report about creation of a cut model, with sufficient size and width to expose part of the skin with dermatitis, to apply another product. The trapezoidal cut, according to positions 3, 6, 9 or 12 hours, corresponding to one of the quadrants, it was performed on the plate of carboxymethylcellulose, pectin, and gelatine coupled to the stoma bag. The entire part of the plate adhered to the skin was adapted to the control product. In the photographic analysis, CorelDRAW 19.0 was used. The lesions were measured in pixels. Result: the cut did not interfere with the adhesion of two parts device board, it made possible the simultaneous application and testing of a new product and the comparison of the healing with the plate. Conclusion: the PPCM is a new strategy for studies of the application of other products for peristomal dermatitis simultaneously in the same patient and demonstrates positive results in its use.
Keywords: Healing; Dermatitis; Surgical Stoma; Computer Assisted Image Processing; Technology; Photography; Stomatherapy